2021
DOI: 10.1002/ece3.7292
|View full text |Cite
|
Sign up to set email alerts
|

The influence of competing root symbionts on below‐ground plant resource allocation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…PCN), might indicate that there are systemic effects induced by mycorrhizal fungi, with a shift in host resource allocation a probable factor. The distribution of plant‐fixed C resources between plants and their competing root symbionts represents a critical gap in our understanding of belowground C dynamics (Bell et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…PCN), might indicate that there are systemic effects induced by mycorrhizal fungi, with a shift in host resource allocation a probable factor. The distribution of plant‐fixed C resources between plants and their competing root symbionts represents a critical gap in our understanding of belowground C dynamics (Bell et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Once established within the roots, the nutritional quality of each feeding site will determine the number of eggs produced by the female nematode (Goheen et al, 2013). Enhanced nutrition of the host through mycorrhizal interactions increases plant tissue nitrogen and phosphorus, and this is then available for acquisition by co-colonising PCN (Schouteden et al, 2015;Bell et al, 2021aBell et al, , 2021b. We found that inoculation with AMF before the introduction of PCN appeared to further increase PCN egg production, with these plants supporting greater PCN populations than PCN-only or PCN-first inoculated plants.…”
Section: Pre-colonisation Of Plants By Amf Enhances Parasitism By Pcnmentioning
confidence: 64%
“…Arrival of the symbiont at the root-soil interface and establishment of symbiosis prior to a subsequent organism may determine the success of both (Werner and Kiers, 2015). In nature, a variety of outcomes are likely where each symbiont colonises different plants in a different order, impacting the success of each plant and possibly the mycorrhizal benefits that they receive (Bell et al, 2021a). In agricultural ecosystems, AMF inoculants are increasingly applied as part of sustainable and/or regenerative approaches to improving crop nutrient access (Thirkell et al, 2017;Elliott et al, 2021), however little consideration has been paid to the costs and benefits of such applications to the plant hosts (Verbruggen et al, 2013;Cely et al, 2016), particularly in multisymbiont scenarios such as those described above.…”
Section: Introductionmentioning
confidence: 99%
“…There will most likely be substantial overlap with metabolic adaptations in plants during the interaction with multicellular organisms such as nematodes or mycorrhizal fungi [2,95]. Also, the different organisms interacting with an individual plant compete for the allocation of resources and trigger specific response patterns with reciprocal effects [96]. Thus, integrating advances in these research areas will contribute to a holistic understanding of plant biotic interactions.…”
Section: Discussionmentioning
confidence: 99%